2022
DOI: 10.1155/2022/2597173
|View full text |Cite|
|
Sign up to set email alerts
|

Protective Role of Amiodarone on Reperfusion Arrhythmia in Patients of Acute Myocardial Infarction with Percutaneous Coronary Intervention Treatment

Abstract: With the development and popularity of percutaneous coronary intervention (PCI), ischemia-reperfusion injury (IRI) has attracted more and more clinical attention. Reperfusion arrhythmia (RA), one of the common manifestations during and after PCI, can affect the postoperative cardiac function of patients with acute myocardial infarction (AMI). Therefore, effective intervention on RA has important clinical significance. This study observed the effect of amiodarone on reperfusion arrhythmia (RA) after percutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Coronary artery disease (CAD) affects approximately 1.72% (1655 per 100,000) of world population and is predicted to become the main cause of disability and death worldwide (Khan et al, 2020 ; World Health Organization, 2021 ). Percutaneous coronary intervention (PCI) is today the major revascularization for patients with CAD (Wang et al, 2022 ) and there are 5 million PCI treatments every year worldwide (Faxon et al, 2018 ). After PCI patients experience a quick recovery and the responsibility of care quickly transfers to them.…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery disease (CAD) affects approximately 1.72% (1655 per 100,000) of world population and is predicted to become the main cause of disability and death worldwide (Khan et al, 2020 ; World Health Organization, 2021 ). Percutaneous coronary intervention (PCI) is today the major revascularization for patients with CAD (Wang et al, 2022 ) and there are 5 million PCI treatments every year worldwide (Faxon et al, 2018 ). After PCI patients experience a quick recovery and the responsibility of care quickly transfers to them.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%